Solve the following lengendre differential equation.
(1-x2)y"-2xy'+l(l+1)y=0
Solution
(1-x2)y"-2xy'+l(l+1)y=0
Can be rewritten as;
y"-x2y"-2xy'+l(l+1)y=0
Solve using power series;
By definition;
y="\\displaystyle\\sum_{n=0}^\n\u221e" anxn
And;
y'="\\displaystyle\\sum_{n=1}^\n\u221e" nanxn-1
y"="\\displaystyle\\sum_{n=2}^\n\u221e" n(n-1)anxn-2
Replace the values in the equation to obtain;
"\\displaystyle\\sum_{n=2}^\u221e" n(n-1)anxn-2-x2"\\displaystyle\\sum_{n=2}^\u221e" n(n-1)anxn-2-2x"\\displaystyle\\sum_{n=1}^\u221e" nanxn-1+l(l+1)"\\displaystyle\\sum_{n=0}^\u221e" anxn
Make all powers of X equal
"\\displaystyle\\sum_{n=0}^\u221e" (n+2)(n+1)an+2xn+"\\displaystyle\\sum_{n=2}^\u221e" -n(n-1)anxn+"\\displaystyle\\sum_{n=1}^\u221e" -2nanxn+"\\displaystyle\\sum_{n=0}^\u221e" l(l+1)anxn
n=0,1,2,3...
When;
n=0
((2.1)a2+l(l+1))x0=0
n=1
3.2a3-2a1+l(l+1)x1=0
n"=\\geq2"
There is a general trend of
((n+2)(n+1)an+2-n(n-1)an-2nan+l(l+1)an))xn=0
All the coefficients of x must equal to zero, therefore;
Using
n=0;a2="\\frac{-l(l+1)a_0}{2.1}"
n=1;a3="\\frac{-(l^2+l-2)a_1}{3.2}"
n"\\geq" 2
an+2="\\frac{(n+l+1)(n-l)a_n}{(n+2)(n+1)}"
This is the recurrence relation.
Using it ;
n=2,
a4="\\frac{(l+3)(2-l)a_2}{4.3}" ="\\frac{(l+3)(l+1)(l)(l-2)a_0}{4!}"
n=3
a5="\\frac{(l+4)(3-l)a_3}{5.4}" ="\\frac{(l+4)(l+2)(l-1)(l)(l-3)a_1}{5!}"
And so on
A pattern for even number is ;
"a_{2n}=\\frac{(-1)^n(l+2n-1)(l+2n-3)...(l+1)l(l-2)...(l-(2n-2))}{(2n)!}"
A pattern for the odd numbers is;
"a_{2n+1}=\\frac{(-1)^n(l+2n)(l+2n-2)...(l+2)(l-1)(l-3)...(l-(2n-1))a_1}{(2_{n+1})!}"
Since y="\\displaystyle\\sum_{n=0}^\u221e" anxn=a0"\\displaystyle\\sum_{n=0}^\u221e" "\\frac{(-1)^n(l+2n-1)(l+2n-3)...(l+1)l(l-2)..(l-(2n-2))}{(2n)!}x^{2n}+a_1\\displaystyle\\sum_{n=0}^\u221e\\frac{((-1)^n(l+2n)(l+2n-2)..(l+2)(l-1)(l-3)...(l-(2n-1))}{(2n+1)!}x^{2n+1}"
Comments
Leave a comment